Associations between Dietary Intake and Urinary Excretion of Sodium, Potassium, Phosphorus, Magnesium, and Calcium - TAKACHI, Ribeka; HABA, Ryota; KUDO, Yoko; KIMIRA, Mitsuru; WATANABE, Shaw (Nippon Eiseigaku Zasshi (Japanese Journal of Hygiene), 2004)
Objectives and Methods: The associations between dietary intake and urinary excretion of sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), and phosphorus (P), and the major dietary sources derived from the urinary minerals were studied in a nutritional survey of 219 Japanese females aged 27-84 years, who completed anthropometric measurements, a one-day dietary record, and a 24hr urine collection. Results: The minerals excreted in the urine were significantly and positively correlated with each other, in which Na excretion was correlated with K and Ca excretion (r=0.490 and r=0.482, respectively, p<0.01) and Ca excretion was correlated with Mg excretion (r=0.526, p<0.01). The ratios of urinary exertion to dietary intake of Na, K, Ca, Mg, and P were 81.5%, 62.7%, 24.5%, 21.7%, and 56.1%, respectively. The dietary intake and the urinary excretion of the minerals expressed per body weight (kg) were significantly and positively correlated (Na, r=0.267; K, r=0.460; Ca, r=0.181; Mg, r=0.245; P, r=0.351, p<0.01). Further examinations using chief component analysis for food intake showed several significant positive correlations, including between Na intake and the intake of vegetables, noodles, and seasonings (r=0.332-0.381, p<0.01); between K, Mg and P intake and the intake of vegetables, fruits, and potatoes (r=0.332-0.533, p<0.01); and between Ca intake and the intake of bread and dairy foods (r=0.428, p<0.01). In addition, significant positive associations were found between Na excretion and the intake of confectionaries, nuts, and seeds (r=0.223, p<0.01). Weak correlations were also found between K excretion and the intake of vegetables (r=0.296, p<0.01); between Ca and P excretion and the intake of meat, oil, and fats (r=0.135, P<0.05; r=0.193, P<0.01, respectively), and between Mg excretion and the intake of bread and dairy foods (r=0.137, P<0.05). Conclusions: Findings from this study indicate that, while urinary excretion of Ca and Mg is unlikely to be a reliable biochemical marker of dietary intake, the levels of urinary excretion of Na, K, and P can be reflective of the intake of salt, vegetables, and meats, respectively. The urinary excretion of the minerals, particularly Na, K, and Ca, may be highly linked to salt intake in Japanese females.